Effect of sequence on the ionization of guanine in DNA - Chakraborty, Rahul; Ghosh, Debashree (Physical Chemistry Chemical Physics, 2016)
The accurate estimation of the ionization energies and understanding the nature of the ionized states of the nucleic acid bases (NABs) are crucial to the understanding of the DNA damage mechanism. The vertical ionization energy (VIE) of guanine is the lowest among the NABs and the ionization energies are strongly affected by the environment, such as solvation and characteristics of nearby NABs. Therefore, we investigate the sequence dependence of the VIEs of guanine in B-DNA. We use the equation of motion coupled cluster method for the estimation of ionization potential with single and double excitations (EOM-IP-CCSD) and density functional theory with dispersion corrected omega B97x-D for the estimation of VIEs. A significant amount of non-additivity or cooperativity, directly proportional to charge delocalization, is noticed in the change in VIE due to the interaction with the nearby NABs. While the change in VIE due to base pairing originates predominantly from charge-dipole interactions, stacking between base pairs is a more complicated balance of dispersion and charge-dipole interactions as well as stabilization due to the delocalization of the positive charge. The long range interactions are however dominated by 1/r(3) distance dependence which shows the major role played by charge-dipole interactions. The extent of localization of positive holes on guanine is also estimated for various sequences.

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).